Method for simulator and scenario design assessing cognitive aspects of fitness to drive - Selina Mårdh (19774506) (2015)
An increasing part of the global population holds a driver’s license. Thus, a greater variety of prerequisites regarding the fitness to drive will occur, increasing the demand for assessing fitness to drive. However, today, there is a lack of internationally agreed upon methods for assessing the fitness to drive. Specifically, there is a need to develop methods to assess cognitive abilities required for driving safely (Hird, Vetivelu, Saposnik, & Schweizer, 2014; Vrkljan, Myers, Crizzle, Blanchard, & Marshall, 2013). The aim of the present project was to develop an objective and scientifically valid method for assessing cognitive aspects of the fitness to drive in a few targeted groups. The aim was to design and implement a mini-simulator for assessing fitness to drive. The target groups included stroke, mild cognitive impairment, ageing and ADHD. A mini-simulator as well as test scenarios for the assessment of cognitive aspects of fitness to drive was designed (see figure 1). A literature review was undertaken regarding previous research on assessing fitness to drive in the targeted groups. The features of the focused diagnosis were studied regarding underlying cognitive impairment with bearing on driving ability. Each scenario of the simulator drive was designed to enable assessment of these cognitive abilities. Examples of diagnose features that were included were risk taking, distraction, impulsivity, inattention, cognitive flexibility, overconfidence, reaction time, responsiveness, neglect, divided attention and memory. A fixed based mini-simulator was built (Figure 1). To assess the cognitive features mentioned, a road stretch was designed. The road included rural road, highway and urban road. The speed limits varied as well as the landscape surrounding the road. Along the road, different, more or less critical situations, were staged enabling assessment of the targeted cognitive abilities. The mini-simulator met the expectations regarding a good implementation of the simulated scenarios. Future research include validation of the mini-simulator and the scenarios. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.30